Extramedullary hematopoiesis contributes to enhanced erythropoiesis during pregnancy via TGF-β signaling - Fu, Yao; Li, Zhengjuan; Lin, Wen; Yao, Jingxin; Jiang, Xiang; Shu, Qun; Mao, Xiaoyuan; Tu, Jiaoqin; Liang, Xinyuan; Li, Liping (Frontiers in Immunology, 2023)
Red blood cells are the predominant cellular component in human body, and their numbers increase significantly during pregnancy due to heightened erythropoiesis. CD71+ erythroid cells (CECs) are immature red blood cells, encompassing erythroblasts and reticulocytes, constitute a rare cell population primarily found in the bone marrow, although they are physiologically enriched in the neonatal mouse spleen and human cord blood. Presently, the mechanisms underlying the CECs expansion during pregnancy remain largely unexplored. Additionally, the mechanisms and roles associated with extramedullary hematopoiesis (EMH) of erythroid cells during pregnancy have yet to be fully elucidated. In this study, our objective was to examine the underlying mechanisms of erythroid-biased hematopoiesis during pregnancy. Our findings revealed heightened erythropoiesis and elevated CECs in both human and mouse pregnancies. The increased presence of transforming growth factor (TGF)-β during pregnancy facilitated the differentiation of CD34+ hematopoietic stem and progenitor cells (HSPCs) into CECs, without impacting HSPCs proliferation, ultimately leading to enhanced erythropoiesis. The observed increase in CECs during pregnancy was primarily attributed to EMH occurring in the spleen. During mouse pregnancy, splenic stromal cells were found to have a significant impact on splenic erythropoiesis through the activation of TGF-β signaling. Conversely, splenic macrophages were observed to contribute to extramedullary erythropoiesis in a TGF-β-independent manner. Our results suggest that splenic stromal cells play a crucial role in promoting extramedullary erythropoiesis and the production of CECs during pregnancy, primarily through TGF-β-dependent mechanisms.